Constructing dialogues and solidarity through “Radio-Cinema” in the Sami-Norwegian colonial context - Normann, Susanne (Coordinamento SIBA - Università del Salento, 2019)
The paper explores an ongoing radio-cinema project in the borderlands between journalism and action research, conducted in the context of colonial conflicts between the indigenous Sami people and the Norwegian state. Interpreting the empirical findings through decolonial and feminist optics, I posit that this radio-cinema project can be seen as a contribution to rethinking methodological creativity in Community Psychology. Through multidirectional dialogues and togetherness, it has mobilized individuals and communities for knowledge construction, creating possibilities for moving from “otherness” towards mutual recognition and affective solidarity